Superior Performance in Liquid Crystal Alignment of Polystyrene-Block-Poly(ethylene-ran-butylene)-Block-Polystyrene-Graft-Maleic Anhydride Film Irradiated with Ion Beam. (1st March 2022) - Kim, Dong Hyun; Lee, Dong Wook; Oh, Jin Young; Won, Jonghoon; Seo, Dae-Shik
Abstract : We studied the change of the surface and liquid crystal (LC) alignment characteristics of Polystyrene- block -poly(ethylene- ran -butylene)- block -polystyrene- graft -maleic anhydride (SEBS-g-MA) film according to ion beam (IB) irradiation. Atomic force microscopy (AFM) analysis revealed that IB irradiation reduces peaks and creates a wrinkled structure. X-ray photoelectron spectroscopy (XPS) analysis revealed that IB irradiation disintegrates the C–C bonds and makes C–O bonds, creating a dipole-dipole interaction, which improves the LC alignment characteristics. Through polarized optical microscopy (POM) analysis, it was found that the best LC alignment characteristics can be obtained after 120 s of IB irradiation. It was found that the anisotropy caused by the ion beam contributed more to the liquid crystal alignment in homogeneous direction than the one caused by the wrinkle structure.